Skip to Content

## Mathematics

# Introducing new Paper mode

Back

Build your own quiz

Browse from millions of quizzes

QUIZ

10th

grade

68%

accuracy

506

plays

Tisha Stoutenburg

4 years

No student devices needed. Know more

11 questions

Show Answers

See Preview

- 1. Multiple Choice30 seconds1 pt
What does (h,k) stand for in the standard circle equation?

(h,k) is the center of the circle

(h,k) is a point on the circle.

(h,k) is a point that we guess and find

(h,k) is the distance of the circle

- 2. Multiple Choice3 minutes1 ptIn the equation (x-3)
^{2}+(y+4)^{2}=121, the radius of the circle is2421112122 - 3. Multiple Choice5 minutes1 ptWhat is the equation of a circle with radius 2 and center (3, 4)?(x+3)
^{2}+ (y+4)^{2}= 2(x-3)^{2}+ (y-4)^{2}= 2(x+3)^{2}+ (y+4)^{2}= 4(x-3)^{2}+ (y-4)^{2}= 4 - 4. Multiple Choice5 minutes1 ptWhat is the equation of the circle?(x+1)
^{2}+ (y +1)^{2}= 3(x+1)^{2}+ (y -1)^{2}= 3(x+1)^{2}+ (y +1)^{2}= 9(x-1)^{2}+ (y -1)^{2}= 9 - 5. Multiple Choice5 minutes1 ptWhat are the coordinates of the center and the radius of the circle with equation:

(x - 4)^{2}+ (y - 3)^{2}= 25^{}^{}?Center (4,3)

Radius = 5 unitsCenter (4,3)

Radius = 25 unitsCenter (-4,-3)

Radius = 25 unitsCenter (-4,-3)

Radius = 5 units - 6. Multiple Choice5 minutes1 ptIn the equation (x-3)
^{2}+(y-2)^{2}=16, the center of the circle is...(3,2)(-3, -2)(-2, -3)(2, 3) - 7. Multiple Choice5 minutes1 pt
The diameter of a circle has length 12. The center is at (-5, 2). Give the equation of the circle.

(x + 5)

^{2 }+ (y - 2)^{2 }= 144(x - 5)

^{2}+ (y + 2)^{2}= 36(x + 5)

^{2 }+ (y - 2)^{2 }= 36(x - 5)

^{2}+ (y + 2)^{2}= 12 - 8. Multiple Choice5 minutes1 pt
What is the equation of the circle.

(x - 3)

^{2 }+ (y + 4)^{2}= 9(x - 3)

^{2 }+ (y + 4)^{2}= 3x

^{2 }+ y^{2}= 9(x - 1)

^{2 }+ (y + 1)^{2}= 7 - 9. Multiple Choice5 minutes1 ptSee PictureABC
- 10. Multiple Choice5 minutes1 pt
What is the center of the circle with equation x

^{2}+ y^{2}= 1?(1, 1)

(0, 0)

(0,1)

not enough information

- 11. Multiple Choice1 minute1 pt(x + 3)
^{2}+ (y - 1)^{2}= 9(x - 3)^{2}+ (y + 1)^{2}= 9(x - 3)^{2}+ (y + 1)^{2}= 3(x + 3)^{2}+ (y - 1)^{2}= 3 - Answer choicesTagsAnswer choicesTags
Explore all questions with a free account

Already have an account?